The Effect of Blood Learning on Moral Development - Chendi Maulana Baharudin Yusup; Triana Lestari (Universitas Muhammadiyah Enrekang, 2021)
The influence of online or online learning one year ago has had a huge impact on education in Indonesia, which of course affects the moral development of children. During the Covid 19 pandemic it had quite a variety of impacts for everyone. The occurrence of sudden changes in daily habitats always causes emotional unpreparedness for each family member, in the development of early childhood behavior. This study involved respondents from several parents, with the data obtained using quantitative. Where respondents from several parents will be presented in the form of a table of research results. Data collection techniques using google form media. The study collected data from the results of the analysis with quantitative data analysis techniques. It can be seen that there is a policy from the government that implements online or online learning that changes all learning activities at educational institutions. Where online or online learning changes moral development in students, especially in early childhood and elementary school age.